Serotonin receptor 4 (5-hydroxytryptamine receptor Type 4) regulates expression of estrogen receptor beta and cell migration in hormone-naive prostate cancer - Yasuhiro Nakamura; Kazue Ise; Yuto Yamazaki; Fumiyoshi Fujishima; Keely M McNamara; Hironobu Sasano (Wolters Kluwer Medknow Publications, 2017)
Background: Estrogens are considered to potentially play some roles in the development and progression of prostate cancer through estrogen receptor beta (ERβ). However, additional factors which could influence the clinical outcome of the patients through modulating these steroid signalings have also been proposed. Among these, increased expression of serotonin receptor especially that of 5-hydroxytryptamine receptor Type 4 (5-HTR4) has been recently proposed to be involved in autocrine/paracrine mechanisms of castration-resistant prostate cancer, but the presence and clinical significance of 5-HTR4 in hormone-naive prostate cancer (HNPC) and its interaction with hormonal signaling pathways have remained virtually unknown. Materials and Methods: We evaluated the status of 5-HTR4 in 112 human HNPC cases (acinar adenocarcinoma) using immunohistochemistry and correlated the findings with clinicopathological features of individual patients and the status of androgen receptor (AR) and ERβ. To further elucidate its underlying mechanisms, androgen-dependent human prostate carcinoma cell line, LNCaP, expressing 5-HTR4, was treated by 5-HTR4 agonist. Results: 5-HTR4 immunoreactivity was detected in 34% of prostate cancer cases examined (38/112) and was significantly correlated with the status of ERβ but not with that of AR and other clinicopathological factors of the patients. Results of in vitro studies demonstrated that 24 h incubation with 5-HTR4 agonist (10 nM) increased the expression level of ERβ messenger RNA compared to controls. 5-HTR4 agonist (100 nM) significantly inhibited LNCaP carcinoma cell migration (P < 0.05). Conclusion: Results of our present study indicated that 5-HTR4 signaling upregulated ERβ expression in HNPCs and could impact on biological processes in HNPC.